"Ich bin zu jung " (Jer 1, 7) - Kingreen, Sarah-Magdalena; Dietz, Alexander; Höhne, Florian (Wege zum Menschen, 2018)
The encounter of different generations is often experienced as full of conflicts - even in the church. The comparison of two TV-shows on pastors displays these conflicts between generations. Equally, there are resources in the togetherness of generations. A resource-oriented approach that makes an appreciative attitude towards one's own and other generations possible, opens up for dialogue and intergenerational learning.